The Genius Loci of Glagah Beach: An Examination of Tourism Space and Place Following the Establishment of Yogyakarta International Airport - Iban, Carlos; Nugroho, Vincentius Tangguh Atyanto; Adi, Ari Mukti Wardoyo; Hermawan, Yusuf (Sekolah Vokasi, Universitas Gadjah Mada, 2025)
The construction of Yogyakarta International Airport (YIA) has triggered rapid, large-scale development in Kulon Progo, Yogyakarta, posing significant risks to the local identity of the adjacent Glagah Beach Tourism Area. This study evaluates the area's genius loci, or spirit of place, to support sustainable, place-based planning. A qualitative approach, including systematic observation and in-depth interviews, was employed. The Genius Loci Model was used to identify the elements that define Glagah's character. Findings reveal that Glagah's genius loci is fragmented, with the lagoon exhibiting a tranquil, positive identity and the coastline reflecting neglect and a negative image. The research also highlights spatial layering, as a contemporary commercial landscape interacts with a historical, sacred space linked to Pakualaman heritage. Glagah's unique physical features, especially its lagoon and breakwater, distinguish it from other regional beaches. The results indicate that a generic, top-down tourism strategy is insufficient. Instead, the complexity of Glagah's identity requires a dual management strategy: one to preserve and enhance the lagoon's positive attributes and sacred heritage, and another to address coastline degradation. This study provides a place-based framework for managing development pressures and protecting a distinctive cultural landscape.